Network-Based Text Message Security System Using the Data Encryption Standard (DES) Algorithm - Horas Aryanto Simanjuntak; Hari Aspriyono; Eko Prasetiyo Rohmawan (Penerbit Jurnal Indonesia, 2022)
UPT. Puskom as practicum manager has the responsibility to provide facilities including applications needed for each course. In this research, the development of a network-based text security system was carried out by implementing one of the cryptographic algorithms that had been packaged into an application so that students could find out the encryption and decryption processes of the Cryptographic algorithm, namely the Data Encryption Standard (DES) Algorithm. A network-based text message security system using the Data Encryption Standard (DES) Algorithm was built using the Visual Basic .Net Programming Language and SQL Server database. The security system built can help keep messages sent secret from the sender to the recipient of the message through the DES algorithm. The encryption process can be carried out by the user who will send a text message to the intended user, who can open the encryption form and select the intended user, the encrypted message will be stored in the database. Meanwhile, decryption can be done by users who receive text messages by opening the decryption form and displaying the messages sent by the message sender. Based on the tests that have been carried out, it can be concluded that the application is capable of encrypting and decrypting text messages using the DES algorithm.